Report of the director-general. International Labour Organisation. 7th Asian Regional Conference, Teheran, December 1971. Report I (2 parts) (International Labour Office, 1971)
1. Agenda for Asia. The social perplexities of the second development decade. The ILO contribution. IV, 48 p